Quality Of Life Among Students In University Of Science And Technology In Jordan - Younis, Maha S. (Journal of the Faculty of Medicine Baghdad, 2008)
Objective: To assess the subjective rating of quality of life of college students in University Of Science And Technology in Jordan as a sample of healthy educated young population through applying the WHOQOL-BREF instrument as a field trial in Jordan and to compare the finding with similar previous study. Methods Three hundreds forms of Arabic version of the self-reporting questionnaire WHOQOL-BREF were distributed to students of third class attending the lecture halls in three colleges (college of Engineering, college of science, college of medicine) in the university campus in AL Ramtha–Jordan from the first of March to first of may 2007., with respect to university regulations,interested participants were only included in the study. Results The rate of response was 100%, the majority of the sample were of single healthy Jordanian nationals of comparable age and sex distribution. About 68.6 %of the students described their quality of life as good or very good while 3o%as acceptable, or fair, the remaining 1.3% reported bad or very bad. Regarding the mean scores distribution of the four domains there were no significant statistical differences between the demographic variables and type of academic discipline. This study findings showed a higher scoring than the previous one done In Iraq. Conclusion The overall psychological profile of college students in Jordan assessed by the WHOQOL-BREF is good manifested through their satisfaction with their life quality ,no important association with given variables was found ,The study revealed better reporting than the Iraqi study reflecting the cultural differences and environmental effects. The investigator recommends re application of the same instrument on other population sample.